Diseño de un programa de adecuación al medio ambiente y seguridad y salud ocupacional para ser aplicado en la producción de cerámicos - Rodríguez Novoa, César Leonardo (2017)
The research aimed to design a fitness program for the environment and occupational health and safety to be applied in the production of ceramics. The methodology used corresponds to the proposal in the ISO and OHSAS standards begins with a preliminary analysis aspects identification and evaluation of impacts. The results indicate that sensitive environmental aspects are the use of resources: water and energy consumption, followed by the emission of particulate matter and toxic emissions. In relation to occupational safety and health relevant aspects related to mechanical and electrical management tools that are the main sources of accidents. Additionally, there is no monitoring of occupational health and about the legal requirements have a 70% compliance. In research it is concluded that the measures proposed corrective and preventive lead to improve the organization towards meeting the requirements of certifiable ISO and OHSAS standards